2015
DOI: 10.3144/expresspolymlett.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

Natural rubber/graphene oxide composites: Effect of sheet size on mechanical properties and strain-induced crystallization behavior

Abstract: Abstract. In order to analyze the influence of the lateral size of graphene oxide (GO) on the properties of natural rubber/ graphene oxide (NR/GO) nanocomposites, three different sized graphene oxide sheets, namely G1, G2 and G3 were used to fabricate a series of NR/GO nanocomposites by latex mixing. The results indicate that adding GO can remarkably increase the modulus of NR. The enhancement of modulus is strongly dependent on the size of GO sheets incorporated. G1 with smallest sheet size gives the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 67 publications
(89 reference statements)
3
34
0
Order By: Relevance
“…Analysis of tan δ peaks showed little to no change in T g with loading but the authors mention that the shape and height of the peak change significantly with incorporation of GO platelets which they attribute to favorable polymer-filler interactions. Wu et al [96] also prepared a series of NR/GO composites filled with different GO sizes through latex co-coagulation technology in order to evaluate the effect of GO size on the mechanical properties of the resulting composites. The storage modulus at 20 • C of neat NR and of the composites filled with 2 phr of GO having three different sizes (92.68, 164.39 and 323.74 nm in the composites) are 1.01, 1.82, 1.71 and 1.52 MPa, respectively.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of tan δ peaks showed little to no change in T g with loading but the authors mention that the shape and height of the peak change significantly with incorporation of GO platelets which they attribute to favorable polymer-filler interactions. Wu et al [96] also prepared a series of NR/GO composites filled with different GO sizes through latex co-coagulation technology in order to evaluate the effect of GO size on the mechanical properties of the resulting composites. The storage modulus at 20 • C of neat NR and of the composites filled with 2 phr of GO having three different sizes (92.68, 164.39 and 323.74 nm in the composites) are 1.01, 1.82, 1.71 and 1.52 MPa, respectively.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…Analysis of tan δ peaks showed little to no change in Tg with loading but the authors mention that the shape and height of the peak change significantly with incorporation of GO platelets which they attribute to favorable polymer-filler interactions. Wu et al [96] also prepared a series of NR/GO composites filled with different GO sizes through latex co-coagulation technology in order to evaluate the effect of GO size on the mechanical properties of the resulting composites. All the studies reported above, point out some discrepancies and contradictory results due to the fact that the composite properties are affected by several factors including the type of particles, the type of polymer, the interfacial interactions and more significantly the filler dispersion that depends on the processing techniques.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…The outstanding mechanical and conductive properties of carbon nanoparticles (CNPs), together with their unique structure and low density, place them among the most common fillers. Carbon nanofiber and carbon nanotubes (CNT) [14][15][16][17][18][19][20] 1,2 , N. Miklósi 1 and its derivatives [21][22][23][24], mainly graphene oxide (GO), have attracted marked interest in the last few years. In biomedical applications, however, the uncertainty surrounding the toxicity of CNTs [14] could affect choices of nanocarbon filler.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, to some extent the formation of lignin‐F51 networks makes the rubber composite compact, which means that there were less empty spaces or voids in the matrix, and the diffusion of solvent molecules would be hindered, thus less solvent get absorbed and the Q f /Q g values would decrease. Since the lower Q f /Q g values mean a higher extent of the interaction between the filler and the rubber matrix . We can conclude that interaction between the lignin‐F51 networks and the rubber matrix become stronger when the lignin‐F5 networks become stronger.…”
Section: Mechanical Propertiesmentioning
confidence: 78%